Cancer-Associated Fibroblasts Induce Epithelial-Mesenchymal Transition in Endometrial Cancer Cells by Regulating Pituitary Tumor Transforming Gene. (16th March 2019) - Wang, Xiaoyun; Sun, Xiwen; Mu, Lin; Chen, Wei
Abstract: Cancer-associated fibroblasts (CAFs) play an important role in the development and progression of cancer by inducing epithelial-mesenchymal transition (EMT). In this study, we investigated the role of CAFs in endometrial cancer (EC) cells. We found that the pituitary tumor transforming gene ( PTTG ) expression was significantly increased in EC cell lines compared to normal human endometrial epithelial cells. Furthermore, CAFs could induce PTTG over-expression and increase EC cell invasion and migration in vitro . In addition, CAFs also induced EMT in EC cells. This study demonstrated that CAFs induced EMT in endometrial cancer cells by regulating PTTG .